JUSTICE AS A BASIS FOR JUDGES TO PROVIDE A BALANCE FOR JUSTICE SEEKERS IN A CRIMINAL CASE SUBMITTED THROUGH A REVIEW - AVRITS (Sekolah Tinggi Ilmu Hukum Awang Long, 2019)
A request for a review should not be allowed to drag on without a solution, the request for review must be limited also, and it does not mean limiting the space for justice seekers to reach justice. The results of the study of the decision of the review conducted by the Supreme Court revealed that the Supreme Court of the Republic of Indonesia through the PK Decision in both the Mochtar Pakpahan and Polycarp cases had largely applied substantial procedural justice by interpreting justice. That every person has the right to get what is his right and use that right to obtain a share in proportion to it in this case the Prosecutor. Substantial procedural justice should be inspired by the flow of natural law, the flow of positivism law and responsive legal flow. In its development, a theory of justice is needed roommates Provides Balanced rewards to the parties in the effort to re-examine the case in the Supreme Court of the Republic of Indonesia. Justice seekers in submitting Efforts Reviews their review as extraordinary legal remedies are not limited only based on the provisions of Article 263 Criminal Procedure Code but are also based on the decision of the Constitutional Court Number 34/PUU-11/2013. However, based on the principle of freedom of judges where judges in accordance with the provisions of Law Number 48 of 2009 concerning Judicial Power are required to explore the values ​​that grow and develop in society. A proof that the judge is required to be Able to implement an article with full care, prudence and fulfill a sense of fairness is the existence of Article 5 of Act Number 48 of 2009 concerning Judicial Power that the judge is obliged to explore the values ​​of justice that grow and develop in the middle of society. Judges must be Able to absorb people's inner aspirations or voices about truth and justice, so that legal certainty can always guard justice, so that the objectives of the law to create justice can be fulfilled.